Genetic Risk Factors in Drug‐Induced Liver Injury Due to Isoniazid‐Containing Antituberculosis Drug Regimens. Issue 4 (5th December 2020) - Nicoletti, Paola; Devarbhavi, Harshad; Goel, Ashish; Venkatesan, Radha; Eapen, Chundamannil E.; Grove, Jane I.; Zafer, Samreen; Bjornsson, Einar; Lucena, M. Isabel; Andrade, Raul J.; Pirmohamed, Munir; Wadelius, Mia; et al.
Abstract : Drug‐induced liver injury (DILI) is a complication of treatment with antituberculosis (TB) drugs, especially in isoniazid (INH)‐containing regimens. To investigate genetic risk factors, we performed a genomewide association study (GWAS) involving anti‐TB DILI cases (55 Indian and 70 European) and controls (1, 199 Indian and 10, 397 European). Most cases were treated with a standard anti‐TB drug regimen; all received INH. We imputed single nucleotide polymorphism and HLA genotypes and performed trans‐ethnic meta‐analysis on GWAS and candidate gene genotypes. GWAS found one significant association (rs117491755) in Europeans only. For HLA, HLA‐B*52:01 was significant (meta‐analysis odds ratio (OR) 2.67, 95% confidence interval (CI) 1.63–4.37, P  = 9.4 × 10 −5 ). For N‐acetyltransferase 2 (NAT2), NAT2*5 frequency was lower in cases (OR 0.69, 95% CI 0.57–0.83, P  = 0.01). NAT2*6 and NAT2*7 were more common, with homozygotes for NAT2*6 and/or NAT2*7 enriched among cases (OR 1.89, 95% CI 0.84–4.22, P  = 0.004). We conclude HLA genotype makes a small contribution to TB drug‐related DILI and that the NAT2 contribution is complex, but consistent with previous reports when differences in the metabolic effect of NAT2*5 compared with those of NAT2*6 and NAT2*7 are considered.